2017
DOI: 10.1080/13607863.2017.1394441
|View full text |Cite
|
Sign up to set email alerts
|

Carer preferences for home support services in later stage dementia

Abstract: These carer preferences concur with emerging evidence on home support interventions for dementia. Respite care, home care and training on managing difficulties provided at home are important components. Carers' preferences revealed the daily challenges of caring for individuals with later stage dementia and the need for tailored and specialised home support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 47 publications
1
51
0
Order By: Relevance
“…Additionally, a previous UK study by Chester et al 9 found that the most preferred home support options for caretakers of people with early‐stage dementia included ‘support with personal feelings and concerns – provided by a trained counselor at home’ and ‘information on coping with dementia – provided by an experienced worker at home’. Furthermore, a study of Kampanellou et al 10 indicated that for the informal caregivers of people with later‐stage dementia, respite care was the most preferred attribute for in‐home support. The informal caregivers in this study did not talk about a need for respite care.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, a previous UK study by Chester et al 9 found that the most preferred home support options for caretakers of people with early‐stage dementia included ‘support with personal feelings and concerns – provided by a trained counselor at home’ and ‘information on coping with dementia – provided by an experienced worker at home’. Furthermore, a study of Kampanellou et al 10 indicated that for the informal caregivers of people with later‐stage dementia, respite care was the most preferred attribute for in‐home support. The informal caregivers in this study did not talk about a need for respite care.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, most of the recruited persons with dementia had early‐stage dementia. When dementia advances, people often become more dependent and demanding in terms of formal and informal care 6‐19 . However, there were informal caregivers included who had their loved ones currently institutionalized or had recently died.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations